The Effect of Antimicrobial Dose of Doxycycline on Glycemic Control in Patients with Diabetes and Moderate Periodontitis after the Phase 1 of Periodontal Treatment - Mohammad Reza Naseh; Jamshid Poursamimi; Sima Hashemipour; Nazanin Zangeneh (مجله دانشکده پزشکی اصفهان, 2014)
Background: There are contradictory results of different studies about the effect of periodontal treatment on metabolic control of diabetes. Due to the importance of management of the patients, the purpose of this study was to examine the effect of periodontal therapy [scaling and root planning (SRP)] with doxycycline on glycemic control in patients with type 2 diabetes mellitus.